2013
DOI: 10.1186/1471-2229-13-35
|View full text |Cite
|
Sign up to set email alerts
|

Grain protein content variation and its association analysis in barley

Abstract: BackgroundGrain protein content (GPC) is an important quality determinant for barley used as malt, feed as well as food. It is controlled by a complex genetic system. GPC differs greatly among barley genotypes and is also variable across different environments. It is imperative to understand the genetic control of barley GPC and identify the genotypes with less variation under the different environments.ResultsIn this study, 59 cultivated and 99 Tibetan wild barley genotypes were used for a genome-wide associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 29 publications
6
90
1
Order By: Relevance
“…On chromosome 2H, we detected some markers that were associated with these two traits in genomic regions that were previously reported to have an impact on yield parameters [62], [66]–[68]. We also discovered two DArT markers, bPb-0994 and bPb-6822 (located on chromosome 2H at 113.2 and 114.4 cM, respectively) associated with grain protein content, which were also found in another study [69]. We also found that the marker bPb-0994, located on chromosome 2H, was highly significant for kernel raw protein content.…”
Section: Discussionsupporting
confidence: 82%
“…On chromosome 2H, we detected some markers that were associated with these two traits in genomic regions that were previously reported to have an impact on yield parameters [62], [66]–[68]. We also discovered two DArT markers, bPb-0994 and bPb-6822 (located on chromosome 2H at 113.2 and 114.4 cM, respectively) associated with grain protein content, which were also found in another study [69]. We also found that the marker bPb-0994, located on chromosome 2H, was highly significant for kernel raw protein content.…”
Section: Discussionsupporting
confidence: 82%
“…Association mapping is widely being utilized for detecting marker-trait association based on the genetic resources routinely used for genetic improvement programs (Font I Forcada et al 2015;Cheng et al 2015;Yan et al 2009;Cai et al 2013). As compared to biparental QTL mapping, association mapping increases the range of natural variation that can be exploited in a single experiment and potential genomic regions could be identified (Jin et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Hence it is not surprising that barley has evolved as a model for seed germination research. The total protein content in barley seed varies between 8 and 15% [1]. The amount and composition of barley proteins influence the suitability and quality of grain for its end uses, with approximately a third of the proteins being present in the final beer [2].…”
Section: Introductionmentioning
confidence: 99%